Organic Single‐Crystalline Microwire Arrays toward High‐Performance Flexible Near‐Infrared Phototransistors. Issue 41 (9th September 2022) - Zhang, Yu; Qiu, Yuchen; Li, Xinyi; Guo, Yangwu; Cao, Shiqi; Gao, Hanfei; Wu, Yuchen; Jiang, Lei
Abstract: Flexible organic near‐infrared (NIR) phototransistors hold promising prospects for potential applications such as noninvasive bioimaging, health monitoring, and biometric authentication. For integrated circuits of high‐performance devices, organic single‐crystalline micro‐/nanostructures with precise positioning are prominently anticipated. However, the manufacturing of organic single‐crystalline arrays remains a conundrum due to difficulties encountered in patterning arrays of dewetting processes at micron‐scale confined space and modulating the dewetting dynamics. Herein, we utilize a capillary‐bridge lithography strategy to fabricate organic 1D arrays with high quality, homogeneous size, and deterministic location toward high‐performance flexible organic NIR phototransistors. Regular micro‐liquid stripes and unidirectional dewetting are synchronously achieved by adapting micropillar templates with asymmetric wettability. As a result, high‐throughput 1D arrays based organic field‐effect transistors exhibit high electron mobility up to 9.82 cm 2  V –1  s –1 . Impressively, flexible NIR phototransistors also show outstanding photoelectronic performances with a photosensitivity of 9.87 × 10 5, a responsivity of 1.79 × 10 4  A W −1, and a specific detectivity of 3.92 × 10 14 Jones. This work paves a novel way to pattern high‐throughput organic single‐crystalline microarrays toward flexible NIR organic optoelectronics. Abstract : 1D organic single‐crystalline arrays with high quality, homogeneous size, and precise position are obtained through a confined assembly method. The field‐effect transistors based on the organic microribbons exhibit high electron mobility up to 9.82 cm 2  V –1  s –1 . Remarkably, flexible near‐infrared phototransistors show superior photoresponse in terms of a high photosensitivity of 9.87 × 10 5, an excellent responsivity of 1.79 × 10 4  A W −1, and a high specific detectivity of 3.92 × 10 14 Jones.